Automatization electrical and magnetic systems development stimulation plants in greenhouses - Kutsenko, Y. (Енергетика і автоматика, 2015)
Grounded Electrical and magnetic systems implications on the development of plants in greenhouse conditions. The recommended design electrical installation with set parameters and functional scheme of automation designed in accordance with the requirements for placing process.